2020
DOI: 10.3390/cells9020316
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adaptive Thermogenesis in Mice on the Treatment of Obesity

Abstract: Obesity and associated metabolic diseases have become a priority area of study due to the exponential increase in their prevalence and the corresponding health and economic impact. In the last decade, brown adipose tissue has become an attractive target to treat obesity. However, environmental variables such as temperature and the dynamics of energy expenditure could influence brown adipose tissue activity. Currently, most metabolic studies are carried out at a room temperature of 21 °C, which is considered a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 135 publications
0
29
0
Order By: Relevance
“…Currently, most of the metabolic and obesity studies are carried out at room temperature of 21 • C, which is considered the thermoneutral zone for adult humans. However, mice subjected to the same temperatures experience a chronic cold, because their thermoneutral zone is 30 • C [137]. It has been reported that mice show differences in metabolic phenotype when housed at room temperature (Ta) (21 • C) vs. at thermoneutrality (30 • C).…”
Section: Other Factors Involved In Obesity Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, most of the metabolic and obesity studies are carried out at room temperature of 21 • C, which is considered the thermoneutral zone for adult humans. However, mice subjected to the same temperatures experience a chronic cold, because their thermoneutral zone is 30 • C [137]. It has been reported that mice show differences in metabolic phenotype when housed at room temperature (Ta) (21 • C) vs. at thermoneutrality (30 • C).…”
Section: Other Factors Involved In Obesity Progressionmentioning
confidence: 99%
“…It has been reported that mice show differences in metabolic phenotype when housed at room temperature (Ta) (21 • C) vs. at thermoneutrality (30 • C). Chronic cold triggers controlled hypothermia and energy expenditure is affected by changes at the physiological (food intake, adipose tissue physiology, and increased adaptive thermogenesis) and metabolic (such as basal metabolism, adaptive thermogenesis, dietary efficiency, insulin secretion, adipose tissue physiology, adipocyte, and vascular inflammation) levels [137]. During exposure to chronic cold (21 • C), total energy expenditure may increase by more than one third, due to the cold-induced thermogenesis required to maintain basal temperature [138].…”
Section: Other Factors Involved In Obesity Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one might expect, adaptive thermogenesis is triggered by cold both at sea level and altitude, and this is partly governed by those sympathetic pathways described above, which will also impact breathing, feeding and food choice, other than through energy expenditure pathways that may promote weight loss indirectly (for review see [149]). Moreover, during acclimation to altitude it is evident that there are differences between acute and chronic adaptive changes to breathing, feeding and food choice.…”
Section: Regulation Of Oxygen Supply Feeding and Food Choice During mentioning
confidence: 99%
“…It is therefore highly important to elucidate the complex pathways of energy homeostasis in order to develop approaches to counteract these dysregulations of metabolism. In addition to advocating individual responsibility regarding energy intake and expenditure, which may present particularly difficult in highly obese individuals 3 , 4 , an endogenous increase of energy expenditure proposes a potential strategy. Regarding this, activation and recruitment of brown adipose tissue (BAT) thermogenesis have been discussed recently 5 8 .…”
Section: Introductionmentioning
confidence: 99%